PENGARUH KONSERVATISME AKUNTANSI DAN LEVERAGE PADA EARNINGS RESPONSE COEFFICIENT - Natalia, Desriyana; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Earnings quality is important for users of financial statements for purposes of the contract and investment decision making. One measure of the quality of earnings is Earnings Response Coefficient (ERC). The purpose of this study to determine the effect of accounting conservatism and leverage on the ERC. Sample research is manufacturing companies listed in Indonesia Stock Exchange. The sample is determined by the method of probability sampling and stratified random sampling technique. The total sample of 236 companies observations. Data analysis using multiple linear regression analysis. Based on the analysis of accounting conservatism negative effect on the ERC and leverage a negative effect on the ERC.
Keywords: accounting conservatism; leverage; earnings response coefficient